How and what to dance - D'Egville, Geoffrey (London Bounty Books, 2008)
How & What to Dance guides you through the etiquette of the ballroom providing invaluable advice on elements such as costume, deportment, how to hold your partner and the discipline of dancing. Step-bystep instructions for all the dances are also included, with footstep diagrams to guide you through the Foxtrot, the Quick Step, the Charleston, the Tango and more.
Instructions for all the popular dances and the etiquette of the ballroom.
Includes index.
Reprinted 1920, 1922, 1929, 1932, 1936, 1941.
First published in 1919 by C. Arthur Pearson Ltd.
Keywords: Ballroom dancing; Dance